High levels of pretreatment and acquired HIV drug resistance in Nicaragua: results from the first nationally representative survey, 2016 - Girón‐Callejas, Amalia (J Int AIDS Soc, 2019)
INTRODUCTION: A nationally representative HIV drug resistance (HIVDR) survey in Nicaragua was conducted to estimate the prevalence of pretreatment HIVDR (PDR) among antiretroviral therapy (ART) initiators and acquired HIVDR among people living with HIV (PLHIV) who had received ART for 12 ± 3 months (ADR12) and ≥48 months (ADR48). METHODS: A nationwide cross‐sectional survey with a two‐stage cluster sampling was conducted from March to November 2016. Nineteen of 45 total ART clinics representing >90% of the national cohort of adults on ART were included. ART initiators were defined as PLHIV initiating or reinitiating first‐line ART. HIVDR was assessed for protease, reverse transcriptase and integrase Sanger sequences using the Stanford HIVdb algorithm. Viral load (VL) suppression was defined as <1000 copies/mL. Results were weighted according to the survey design. RESULTS AND DISCUSSION: A total of 638 participants were enrolled (PDR: 171; ADR12: 114; ADR48: 353). The proportion of ART initiators with prior exposure to antiretrovirals (ARVs) was 12.3% (95% CI: 5.8% to 24.3%). PDR prevalence to any drug was 23.4% (95% CI: 14.4% to 35.6%), and 19.3% (95% CI: 12.2% to 29.1%) to non‐nucleoside reverse transcriptase inhibitors (NNRTI). NNRTI PDR was higher in ART initiators with previous ARV exposure compared with those with no exposure (76.2% vs. 11.0%, p < 0.001). Protease inhibitors (PI) and integrase strand transfer inhibitors PDR was not observed. VL suppression rate was 77.8% (95% CI: 67.1% to 85.8%) in ADR12 and 70.3% (95% CI: 66.7% to 73.8%) in ADR48. ADR12 prevalence to any drug among PLHIV without VL suppression was 85.1% (95% CI: 66.1% to 94.4%), 82.4% to NNRTI and 70.2% to nucleoside reverse transcriptase inhibitors (NRTI). ADR48 prevalence to any drug among PLHIV without VL suppression was 75.5% (95% CI: 63.5% to 84.5 %), 70.7% to NNRTI, 59.4% to NRTI and 4.6% to PI. CONCLUSIONS: Despite implementation challenges yielding low‐precision HIVDR estimates, high rates of NNRTI PDR were observed in Nicaragua, suggesting consideration of non‐NNRTI‐based first‐line regimens for ART initiators. Strengthened HIVDR monitoring, systematic VL testing, and improved ART adherence support are also warranted.